(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The author’s team investigated the role of the state in regulatory processes regarding the competitive relations of the regional markets of residential real estate in the regions of Ukraine. The modern tendencies and situation that dominate the housing market in the country and its regions are shown. After all, the housing market in the country is not able to fully cope with self-regulatory processes independently, it was also proved the need for interference from the side of the state in its processes occurring in the regions. Efficiently implemented and directed infrastructure significantly increases the level of competitiveness of local markets, and also provides a process of continuous reproduction of their competitive advantages. The main problem issues that are taking place in the process of realization of state antimonopoly supervision over market processes are singled out. The existing and offered innovative ways of analysis and estimation of market weight are investigated. Clear, priority directions of ensuring the implementation of antitrust policy by the state are defined. The toolkit is proposed that will help to control the activity of regional housing markets. The purpose of the paper is to thoroughly study the processes of organizing and regulating the state of the processes of competitive relationships between the subjects of the residential real estate market in a regional dimension. A serious economic tool for regulating the competitiveness of the region is the taxation and lending of enterprises, pricing, depreciation policy of enterprises. With the help of taxation, the state regulates and influences economic processes within the region and the state as a whole. The state uses a tax mechanism for economic impact on public production and its structure by increasing or reducing the mass of tax revenues. With the change in the form of taxation, tax rates, tariffs, and the exemption from taxation of certain types of activities, the state can give impetus to the growth or retardation of economic activity, the development of priority types of economic activity. In the presence of various forms of transformation into market economic relations, it is necessary to form a fundamentally new model of the mechanism of lending. It should consider the fact that, together with the bank forms of the loan must be used and off-bank. Speaking about pricing, it should be noted that the state should establish recommended price limits for economic entities. In some cases, a maximum price is set above which it is impossible to sell the product or provide services, in other cases – the minimum price below which it is impossible to sell the product. Enterprises must adhere to government prices. The structural reorientation of the Ukrainian economy is closely linked with the use of the scientific and technological process, with the latest methods and forms of organization of management of innovative processes, the expansion of adaptation to new methods on the forms of construction.